2022
DOI: 10.1186/s12903-022-02414-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bleaching applications on stained bulk-fill resin composites

Abstract: Background The structure of bulk-fill resin composites differs from that of their conventional counterparts, but how this difference affects the color stability of the former after staining and bleaching is unclear. Accordingly, this study was aimed at investigating color change in nine bulk-fill resin composites and one nanohybrid resin composite treated with hydrogen peroxide and carbamide peroxide after staining with tea, coffee, and red wine. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The main feature that sets this restorative material apart is its decreased deformation following the polymerization process [11], as well as its ability to recover for elevated C-factors of some dental cavities in teeth located in the posterior region, which results in a significant reduction in chairside working duration [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main feature that sets this restorative material apart is its decreased deformation following the polymerization process [11], as well as its ability to recover for elevated C-factors of some dental cavities in teeth located in the posterior region, which results in a significant reduction in chairside working duration [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there has been numerous research on the effects of various beverages on resin composites' colour consistency, there is not enough information available on the colour consistency of bulk-fill composite resins, which were developed for the installation of significantly thicker increments. [14] The goals and objectives of the systematic review were to review various studies on the colour changes of bulkfilled composites. The following were the goals: i) In the presence of a dye substance, various beverages, drinks, and oral fluids examine the colour consistency of various bulk-filled composite samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe was placed in the center of the specimens and the "L*, C*, H*, a*, and b*" values were measured separately on a white and black background. These values were measured thrice and the mean values were recorded (Erturk-Avunduk et al, 2022). The spectrophotometer was recalibrated according to the manufacturer's instructions after 9 measurements.…”
Section: Color Measurementmentioning
confidence: 99%
“…However, some other studies have reported significant effects of these agents on composite resin materials. Differences in these effects have been attributed to the volume of the resin matrix and the filler type [14][15][16].…”
Section: Introductionmentioning
confidence: 99%